Strategi Pembelajaran Pendidikan Agama Kristen - Markus Oci (Sekolah Tinggi Theologia Nazarene Indonesia, 2015)
Teaching and learning activities cannot be seperated from the roles of teacher or educator. Teaching and learning activities will be ideal if there were teacher, learner and some proponent factors such as: material, purpose, strategy, medium and an evaluation. Effective and efficient teaching and learning activities are always connected with those kind of proponent factors. Due to the fact that the effectiveness and efficiency of teaching and learning process must be fit with learning purpose. The success of teaching and learning activities are dependent on strategy and the ways that are used by the teacher in the learning process.